Comprehensive behavioral characterization and impaired hippocampal synaptic transmission in R1117X Shank3 mutant mice - Jingyao Gao; Shumin Wu; Jingxuan Yang; Tong Ye; Jie Yang; Wenhua Shen; Xingwang Chen; Li Huang; Ruiqi Pang; Ping Lin; Jiahe Lin; Yi Zhou; et al. (Translational Psychiatry)
Abstract Mutations in the Shank3 gene are strongly associated with various neurodevelopmental disorders, particularly autism spectrum disorder (ASD). The R1117X mutation, which results in truncated SHANK3 protein, has been implicated in dysfunctions in the striatum and cortex. However, its effects on hippocampal function remain poorly understood. In this study, we performed a comprehensive behavioral and synaptic analysis of homozygous R1117X Shank3 mutant mice. These mice exhibited deficits in sensory gating, motor coordination, and pain perception, alongside severe anxiety in novel environment. Additionally, they showed significant impairments in learning and memory, as well as abnormal spontaneous fine motor behaviors. Histological analysis revealed morphological changes in the hippocampus, which were coupled with deficits in synaptic transmission and plasticity. Notably, we observed a downregulation of glutamatergic receptors in the hippocampus, particularly NMDA receptor subtypes. Taken together, these findings demonstrate that the homozygous R1117X Shank3 mutant mouse represents a valuable model for investigating schizophrenia associated with intellectual disability. The altered hippocampal morphology, impaired synaptic function, and deficits in learning and memory observed in this model provide new insights into the underlying mechanisms of Shank3-related neurodevelopmental disorders.